Accelerating sustainable transformation in sub-Saharan Africa: the role of clean energy, digitalization, foreign direct investment, and industrialization - Abdi, Abdikafi Hassan; Zaidi, Mohd Azlan Shah; Hassan, Mandeq Abdullahi; Ahmed, Seadya (Frontiers in Environmental Science, 2025)
IntroductionSub-Saharan Africa (SSA) faces growing pressure to align economic progress with environmental sustainability, as the region contends with climate stress, industrial expansion, and resource-driven growth. Yet, there remains a limited understanding of the combined influence of clean energy, digitalization, foreign direct investment (FDI), and industrial development on the region’s sustainable transition.MethodsThis study explores the association between clean energy usage, FDI, economic growth, digitalization, industrialization, urbanization, and environmental sustainability across 38 SSA countries from 2001 to 2020. It applies econometric techniques including the pooled mean group estimator and method of moments quantile regression.ResultsThe analysis affirms the transformative potential of renewable energy, which significantly reduces both ecological footprints and environmental pollution. FDI demonstrates dual effects-fostering technological improvements while amplifying ecological footprints through resource-intensive investments. Economic growth is consistently related to increased emissions and ecological impact. Strikingly, digitalization proposes promising pathways for sustainability, while industrialization and urbanization exacerbate environmental challenges. Quantile regression results reveal that these effects vary across different levels of environmental impact. The Dumitrescu–Hurlin panel causality test affirms bidirectional causalities in at least one cross-section.DiscussionSustainable development in SSA requires prioritizing renewable energy adoption, regulating FDI to align with environmental goals, integrating sustainability into economic and industrial policies, and expanding digitalization for smarter resource management.